A fluorescence-positioned hybridization chain reaction system for sensitive detection of Salmonella in milk. Issue 15 (31st March 2020) - Yang, Guotai; Yu, Shuang; Liu, Yang; Huang, Jin; Li, Qianying; Aguilar, Zoraida P.; Xu, Hengyi
Abstract : In this study, a fluorescence-positioned hybridization chain reaction (HCR) system for the detection of single-stranded DNA (ssDNA) specific to Salmonella was developed. Abstract : In this study, a fluorescence-positioned hybridization chain reaction (HCR) system for the detection of single-stranded DNA (ssDNA) specific to Salmonella was developed. Target ssDNA captured by magnetic beads was used to trigger the HCR, forming multiple double-stranded DNAs (dsDNAs). SYBR Green I was applied to intercalate with the minor groove of the dsDNA forming MBs + dsDNA + SYBR Green I. Magnetic separation was used to isolate the MBs + dsDNA + SYBR Green I from the excess reagents before recording the fluorescence intensity (FI). This fluorescence-positioned HCR method for the quantitative detection of Salmonella showed a limit of detection (LOD) as low as 4.2 × 10 1 CFU mL −1 in 0.01 M phosphate-buffered saline (PBS). When the method was applied in spiked milk samples, the LOD was recorded at 4.2 × 10 2 CFU mL −1 . The fluorescence-positioned HCR method provided a modification-free and fluorescence-positioned strategy for sensitive detection of target DNA which holds promise for sensitive and selective bacterial detection.